Using free web hosting services to design community websites for novice web designer / Farah Ahlami Mansor … [et al.] - Mansor, Farah Ahlami; Hashim, Mimi Zazira; Muhammad, Norrini; Wan Azib, Wan Nor Hazimah (2018)
There are many purposes of websites development. Different kinds of websites have different purposes depending on its targeted users. Some websites are designed for selling products, providing practical information or sharing entertainment. This study focuses on the usability of informative and practical information website on educational purposes. The aim of an information centric website is to convey specific and helpful information for reader so that the users learn something new or understand a topic better. According to Williamson & Parolin (2012), web design is the process of collecting ideas, aesthetically arranging and implementing them, guided by certain principles for a specific purpose with the intention of presenting the content on electronic web pages, which the end-users can access through the Internet with the help of a web browser. Free web hosting can be described as programs that allow users to design and develop their own website through an easy interface that takes all programming and coding work out (Prodan & Ostermann, 2009). Users can produce an interesting and functional website without having to understand technicalities aspects like code and error.